Creation of Interactive Question Card Media to Enhance Creative Thinking Abilities of Third Grade Elementary Student - Ramdaniati, Ramdaniati; Irmaningsih, Irmaningsih; Rijalul , Muh. (Journal of Educational Sciences, 2025)
Creative thinking is a crucial skill for the 21st century; however, elementary school children often struggle to develop it due to monotonous teaching methods and limited educational resources. This study aimed to develop and evaluate interactive question card media to enhance the creative thinking skills of third-grade students at SDN 49 Kota Bima. The research utilized a Research and Development (R&D) methodology, specifically the ADDIE (Analysis, Design, Development, Implementation, Evaluation) framework. There were 22 students in all, with 7 in a small group trial and 15 in a large group trial. Material and media specialists did the validation, students looked at how practical it was, and the N-Gain formula was used to compare pretest and posttest scores to find out how effective it was. The results showed that the tests were very valid, with scores of 92.50% and 95.22%. They were also very practical, with scores of 89.29% and 88.64%. The N-Gain of 0.353 showed that they were only moderately effective. As a result, interactive question card media are real, useful, and effective as other tools for teaching in elementary school classrooms.